Legal Protection of Book Creators Against Digitalization in the Perspective of the Use of AI - Paramita, Dinah Ayu; Tampubolon, Veronicatiur Maulina; Choerunnisaa, Rizka; Hidayat, Dudung; Handiriono, Raden (Indonesian Journal of Advanced Research, 2025)
The development of artificial intelligence (AI) technology has made the process of digitizing books easier, such as converting printed books into digital form. While this makes it easier to access and store information, AI-assisted digitization also poses a risk of copyright infringement, mainly if it is carried out without permission from the author or the book's copyright holder. The problem is how the law in Indonesia, especially Law No. 28 of 2014 related to Copyright, protects book creators' rights in the face of digitalization practices involving AI. This research aims to question how the regulations governing copyright protection for books digitized with the help of AI and the implementation of Law No. 28 of 2014 concerning Copyright on the digitization of books with the help of AI. This research uses a normative juridical method, with a legislative approach and literature study. The results of the implementation of this study indicate that although copyright law has regulations for the protection of copyrighted works, including books, no regulation specifically discusses the use of AI in the digitization process. To protect copyright in the digital era, regulations must be strengthened and public awareness increased.